Maternal and neonatal outcomes of pre-eclampsia in African black women, South West Nigeria (2015)
Aim: To evaluate the biophysical, biochemical and clinical characteristics of pre-eclamptic pregnancies as a suitable approach to access and manage pregnancy at risk of pre-eclampsia. Methods: 89 pregnant women with preeclampsia were investigated longitudinally at prepartum and postpartum. The biophysical, biochemical and clinical variables of both mother and neonate of pre-eclamptic pregnancy obtained by standard procedures were compared with the normotensive pregnant controls. Results: Mean gestational ages were significantly lower in pre-eclampsia than in control group (P < 0.001). Caesarean section operations were significantly higher in the group with pre-eclamptic pregnancy compared with the control group (P < 0.05). Pre-eclamptic group recorded significantly higher maternal and neonatal mortality rates than the normotensive controls (P < 0.05). The mean placenta weight, one and five minutes apgar score of neonates of preeclamptic pregnancy were significantly lower compared with the controls (P<0.05). Systolic and diastolic blood pressures at each of the study periods in pre-eclamptic group were significantly elevated compared with the nomortensive pregnancy (P< 0.001). Pre-eclamptic pregnancies had varying degrees of significant microalbuminuria compared with the controls (P < 0.001). Conclusion: Low birth weight, high maternal and neonatal mortality rates, and Cesarean section, low gestational age, apgar scores, placenta weight, elevated blood pressures and microalbuminuria occur more frequently in pre-eclampsia than in healthy normotensive pregnancy.